The clinical effect of lumbar puncture in normal pressure hydrocephalus. Issue 1 (January 1982) - Wikkelsø, C; Andersson, H; Blomstrand, C; Lindqvist, G
Abstract : Owing to all the difficulties involved in selecting patients with normal pressure hydrocephalus for shunt-operation, a cerebrospinal fluid-tap-test (CSF-TT) is introduced. Psychometric and motor capacities of the patients are measured before and after lumbar puncture and removal of 40-50 ml CSF. Patients fulfilling criteria for normal pressure hydrocephalus were compared to patients with dementia and atrophy shown by computed tomography. Normal pressure hydrocephalus patients showed temporary improvement after lumbar puncture. The extent of the temporary improvement appeared to be well correlated with the improvement after shunt operation. Accordingly, the CSF-TT seems to be of value when selecting those patients who will probably benefit from a shunt operation.